Institutional and Economic Determinants of Public Health System Performance - Mays, Glen P. (© American Journal of Public Health 2006, 2006)
Objectives. Although a growing body of evidence demonstrates that availability and quality of essential public health services vary widely across communities, relatively little is known about the factors that give rise to these variations. We examined the association of institutional, financial, and community characteristics of local public health delivery systems and the performance of essential services. Methods. Performance measures were collected from local public health systems in 7 states and combined with secondary data sources. Multivariate, linear, and nonlinear regression models were used to estimate associations between system characteristics and the performance of essential services. Results. Performance varied significantly with the size, financial resources, and organizational structure of local public health systems, with some public health services appearing more sensitive to these characteristics than others. Staffing levels and community characteristics also appeared to be related to the performance of selected services. Conclusions. Reconfiguring the organization and financing of public health systems in some communities—such as through consolidation and enhanced intergovernmental coordination—may hold promise for improving the performance of essential services.